2014
DOI: 10.1007/s11999-013-3005-8
|View full text |Cite
|
Sign up to set email alerts
|

Frozen Section versus Gross Examination for Bone Marrow Margin Assessment During Sarcoma Resection

Abstract: Background Complete resection is critical for local control of primary bone sarcomas. Intraoperative consultation, including frozen section of bone marrow margins, frequently is used to aid in this goal. Questions/purposes We therefore sought to determine (1) how often intraoperative frozen section of a bone marrow margin correlates with inspection of the gross split specimen and, in cases of a discrepancy, what clinical decision is made; and (2) how well each of these assessments agrees with the final patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Prior to the era of current advanced imaging modalities, intraoperative evaluation of the bone marrow by frozen section was the norm in surgical treatment of bone sarcomas [19]. This is time consuming, needs the availability of a dedicated pathologist for assessing the sample during surgery, and adds an additional financial cost to treatment [20]. Advances in imaging have improved our ability to accurately assess the extent of tumor on MRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the era of current advanced imaging modalities, intraoperative evaluation of the bone marrow by frozen section was the norm in surgical treatment of bone sarcomas [19]. This is time consuming, needs the availability of a dedicated pathologist for assessing the sample during surgery, and adds an additional financial cost to treatment [20]. Advances in imaging have improved our ability to accurately assess the extent of tumor on MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in imaging have improved our ability to accurately assess the extent of tumor on MRI. This can help reduce or obviate intraoperative frozen section sampling [20]. Anderson et al in a study of 142 patients concluded that frozen section can be omitted to determine the disease status at the osteotomy site [20] though they did suggest examination of the split gross specimen as an adjunct to clinical and radiological findings to ensure negative margins.…”
Section: Discussionmentioning
confidence: 99%
“…A 3–5 cm all around macroscopic margins were achieved. An intra-operative frozen section histological examination for microscopically clear margins was omitted to save operative and general anesthetic time [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the bandsaw disrupts attached soft tissues, and there are limitations to the number of planes that can be sectioned. Even so, gross evaluation of the split bone sarcoma resection specimen performed during surgery can help to confirm a negative margin with enough confidence to obviate the need for frozen section, or it may trigger a surgeon's removal of additional tissue [1]. Occasionally, intraoperative gross assessment may help to target the best area to be sampled for frozen section with histologic evaluation.…”
Section: Sara O Vargas MD Staff Pathologist Boston Children's Hospitalmentioning
confidence: 99%